An Econometric Analysis of the Impact of Contemporary Climate Smart Technologies on Global Carbon Dioxide Emissions - Chiba, Moffat (Journal of Climate Change Society, 2025)
Climate smart technologies are part and parcel of the low-carbon technological climate change package, which have entered the arena for climate policy discussions since the 1980s. Past efforts at tackling climate change have been around since 1980 and the need to create a low carbon economy has been at the forefront of climate change global discussions. Against this background, this paper provides an econometric analysis of the impact of climate smart technologies on global carbon dioxide emissions. It quantitatively traces the progress that has been made globally in reducing carbon dioxide emissions considering that the 2050 net-zero emissions deadline is only two and a half decades away. The paper considers carbon dioxide due to the observation that it is the most significant greenhouse gas whose emissions currently stand at 37 gigatons per annum. Making use of graphite, zinc, silver global production annual trends, global land use changes and the changing trends of global forest area cover of global data running from 1990 to 2023 to generate the formula, Log(co2) = β0 + β1Logforest + β2Log(graphite) + β3Log(landuse) + β4log(silver) + β5dlog(zinc) +ε, in EViews 7, the study found that a 1% increase in forest, graphite, landuse, silver and zinc technologies yields a 95% reduction in carbon dioxide emission. There is positive progress in attempts at reducing carbon dioxide emissions. The study therefore recommends nation-states to increase and gear-up their climate smart efforts to achieve net-zero GHGs emissions by 2050.